Pengaruh Inovasi Produk dan Promosi Penjualan terhadap Keunggulan Bersaing pada McDonald’s di Jakarta - Nurbintang, Fitra; Siti Julaeha, Lia (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
McDonald's is one of the largest franchises that has rapidly expanded in Indonesia and internationally, becoming one of the fast-food restaurants that is still favored by people both from Indonesia and abroad. Despite the emergence of numerous competitors, McDonald's continues to thrive and excel with various strategies and innovations. One of them is the BTS Meal project, which resulted in a 57% increase in net sales. The research method used is a quantitative type with a descriptive nature, involving the distribution of questionnaires to 96 respondents who have purchased McDonald's products in Jakarta at least once. The sample for this research was determined using the Lemeshow Formula. This study utilizes multiple linear regression analysis and has fulfilled tests for instruments and classical assumptions, processed using the Statistical Package for Social Science (SPSS) version 25 software. The results of the regression analysis show that the variables of product innovation and sales promotion have significance values of <0.001. Product innovation and sales promotion together have a significance value of 0.000, contributing 62.9% to competitive advantage, while the remaining 37.1% is influenced by other factors. The conclusion drawn from the research is that product innovation significantly affects competitive advantage. Meanwhile, sales promotion significantly influences purchasing decisions. Product innovation and sales promotion, when considered together, significantly impact competitive advantage.